2013
DOI: 10.3758/s13420-013-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Get out of the corner: Inhibition and the effect of location type and number on perceptron and human reorientation

Abstract: Spatial learning and navigation have frequently been investigated using a reorientation task paradigm (Cheng, Cognition, 23(2), 149-78, 1986). However, implementing this task typically involves making tacit assumptions about the nature of spatial information. This has important theoretical consequences: Theories of reorientation typically focus on angles at corners as geometric cues and ignore information present at noncorner locations. We present a neural network model of reorientation that challenges these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Some of our previous research using perceptrons has demonstrated this paradigm. For instance, after using simulations and formal analyses to establish strong general links between perceptrons and associative learning (Dawson, 2008), and to then use these networks to model phenomena in a particular associative learning task, reorientation (Dawson et al, 2010), perceptrons generated interesting hypotheses concerning reorientation which were then explored and confirmed experimentally (Dupuis & Dawson, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Some of our previous research using perceptrons has demonstrated this paradigm. For instance, after using simulations and formal analyses to establish strong general links between perceptrons and associative learning (Dawson, 2008), and to then use these networks to model phenomena in a particular associative learning task, reorientation (Dawson et al, 2010), perceptrons generated interesting hypotheses concerning reorientation which were then explored and confirmed experimentally (Dupuis & Dawson, 2013b).…”
Section: Discussionmentioning
confidence: 99%